POLA KONSUMSI PANGAN, STATUS GIZI, KADAR HEMOGLOBIN TERHADAP PRESTASI BELAJAR SISWA SMK KUPANG - Frida Pay (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
A good nutritional status is one of the determining factors for the success of national development. School-age adolescents need to get good attention because in addition to their large number, which is around 30% of the total population, health and nutrition programs in this group have a wide impact not only today, but directly affect the quality of human resources in the future. This is to analyze the effect of food consumption patterns, nutritional status, and hemoglobin levels on learning achievement of vocational high school students. This type of research is analytic observational with cross sectional design. The number of samples in this study were 206 students. The results showed that food consumption patterns that greatly influenced learning achievement were the amount of food, namely energy with p = <0.05; p = 0.000 and protein p = <0.05; p = 0.009 while the food consumption pattern that had no effect was the type of food p = <0.05; p = 0.530 and the feeding frequency p = <0.05; p = 0.027; Nutritional status is also very influential on learning achievement, namely p = <0.05; p = 0.005. Hemoglobin levels have an effect on learning achievement, namely p = <0.05; p = 0.007. The suggestion in this research is to increase vocational students' knowledge about food knowledge with nutrition and to help provide motivation to increase the success of learning achievement. Keywords: Food Consumption Pattern, Nutritional Status, Hemoglobin Level, Learning Achievement